(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background & Objectives- Sepsis, is caused by dysregulated host response that leads to multiple organ dysfunction. Complications of sepsis being so grave, it becomes important to address it in a community setting as sepsis always presents itself as a reason for clinical deterioration of preventable and common diseases. Methods- Analysis of in-patient records of 49,107 at a tertiary care centre in India were analysed from years 2016-2020, to study correlation of sepsis with various comorbidities such as Diabetes, Hypertension, Coronary artery disease, Cerebrovascular accident and Thyroid; and also, to study the death toll occurring due to sepsis. Results- Sepsis has a higher prevalence in the vulnerable age groups that is > 60 years followed by < 20 years of age. Sepsis is observed more in males (56.32%) than females (43.68%). Sepsis was found to have a statistically significant association (P<0.0001) with Diabetes, Hypertension, Coronary artery disease and cerebrovascular accident. 38% of total deaths that occurred in the hospital were due to sepsis. 68.9% of patients who died due to sepsis were ICU cases. Interpretations & Conclusions- Septic patients are 9 times more prone to death than non-septic patients in an Intensive care unit. There is no statistically significant association between thyroid disorder and sepsis (P=0.38). Generally, a researcher would expect diabetes to be a major contributor to sepsis, however our paper reports 70% of total septic cases to be non-diabetic ones. Sepsis itself is caused due to microbial infections but the comorbidities contributing to its prevalence are non-infectious in nature.